Students’ ethnographic practices reflect critical conscious research in a multicultural college class - Pace, Josefa (Journal of Interdisciplinary Studies in Education, 2019)
Teaching the Issues in Multicultural Education course at a New York Statecollege with a diverse population highlights the necessity to address currentcomplex societal topics. The course’s methodological framework is ingrained inthe democratic ideas of tolerance, justice, and agency. This article describes aninterdisciplinary college course, which allows students to practice ethnographicmethods in order to re-conceptualize and confront stereotypes and socialconstructions. Through a formal mini ethnographic project, studentsdocumented their observations and interactions of a religious institution within acommunity. The oral and written presentations from this field-based researchdisplayed that students became critically conscious of others’ communalpractices when they investigated the sites from a first-hand account.